Diverse Streptococcus pneumoniae strains drive a MAIT cell response through MR1-dependent and cytokine-driven pathways. - Kurioka, A; van Wilgenburg, B; Javan, R; Hoyle, R; van Tonder, A; Harrold, C; Leng, T; Howson, L; Shepherd, D; Cerundolo, V; Brueggemann, A; Klenerman, P (Oxford University Press, 2017)
Mucosal Associated Invariant T (MAIT) cells represent an innate T-cell population which can recognize ligands generated by the microbial riboflavin synthesis pathway, presented via the major-histocompatibility-complex (MHC) class I-related molecule MR1. Streptococcus pneumoniae (the 'pneumococcus') is a major human pathogen that is also associated with commensal carriage, thus host control at the mucosal interface is critical. The recognition of pneumococci by MAIT cells has not been defined, nor have the genomics and transcriptomics of the riboflavin operon. We observed robust recognition of pneumococci by MAIT cells, using both MR1-dependent and independent pathways. The pathway used was dependent on the antigen-presenting cell. The riboflavin operon was highly conserved across a range of 571 pneumococci from 39 countries dating back to 1916, and different versions of the riboflavin operon were also identified in related Streptococcus species. These data indicate an important functional relationship between MAIT cells and pneumococci.